"دور التمكين الإداري في تعزيز الأداء المتميز للمورد البشري دراسة حالة مديرية الضرائب –الوادي " - فتيحة منقع; دنيا خوخو; عواطف رضواني; مباركة لعقاب (university of eloued جامعة الوادي, 2024)
"تهدف هذه الدراسة الى معرفة أثر التمكين الإداري بأبعاده الستة (تفويض السلطة، مشاركة المعلومات، التدريب، فرق العمل، التحفيز) على الأداء المتميز للمورد البشري، ومن اجل تحقيق هذا الهدف قمنا بدراسة ميدانية لمديرية الضرائب -الوادي-حيث تم الاعتماد على المنهج الوصفي التحليلي، وبلغت العينة 38 مفردة، وتم معالجة البيانات بواسطة البرنامج الاحصائي SPSS، وقد توصلت الدراسة الى النتائج التالية -توجد علاقة ارتباطية موجبة بين التمكين الإداري والإداء المتميز للمورد البشري بمديرية الضرائب لولاية الوادي -لا يوجد أثر ذو دلالة إحصائية لجل ابعاد التمكين الإداري (مشاركة المعلومات، التدريب، فرق العمل، التحفيز) على الأداء المتميز للمورد البشري إلان هناك أثر ذو دلالة إحصائية لبعد تفويض السلطة على الأداء المتميز للمورد البشري في المؤسسة محل الدراسة. -لا توجد فروق ذات دلالة إحصائية لإجابات افرد عينة الدراسة حول دور التمكين الإداري والأداء المتميز للمورد البشري تعزى للمتغيرات المستوي التعليمي والخبرة. " "This study aims to determine the impact of administrative empowerment through its five dimensions (delegation of authority, information sharing, training, teamwork, and motivation) on the exceptional performance of human resources. To achieve this goal, a field study was conducted at the Tax Directorate in El Owed, employing the descriptive-analytical method. The sample consisted of 38 individuals, and the data was processed using the statistical program SPSS. The study - there is a positive correlation between administrative empowerment and the outstanding performance of the human resource in the valley state Tax Directorate. -there is no statistically significant effect for most of its dimensions: empowerment, administrative empowerment (information sharing, such as training, work teams, and motivation) on the Ou tstanding performance of the human resource. However, there is a statsistically significant effect for the dimension of delegation of authority on the outstanding performance of the human resource in the institution under study .there aee no statistically significant differences between the answers and sample members. Concerning admimstrative empowerment and outstanding performance (for the human resource) due to the educational level variable And experience. "
Keywords: تمكين اداري، تفويض السلطة، فرق عمل، أداء متميز، مشاركة معلومات administrative empowerment ،Delegation of authority ،work teams ، outstanding performance، Share information